New Strategies for the Development of Multifunctional Suture Threads. Issue 1 (16th April 2021) - Tranquillo, Elisabetta; Bollino, Flavia
Abstract: Surgical site infection (SSI) is one of the most frequently reported types of hospital‐acquired infections, associated with severe morbidity and sometimes mortality. It leads to an increase in the clinical and economic burden of surgery, due to the direct costs incurred by prolonged hospitalization, diagnostic tests, outpatient visits, systemic antibiotic treatments, and often reoperations. The SSI is frequently caused by the suture threads material which can become an infection vector. The present mini‐review shows how the research is bringing new skills and knowledge in the design of new suture threads for SSI prevention and the wound healing process improvement.